(untitled) (Web of Teachers: Inderscience Research, 2026)
In contemporary society, the requirements for preschool education institutions are steadily increasing, which necessitates the implementation of innovative management methods not only to enhance the quality of education but also to foster effective cooperation among staff members. The ability of employees to work collaboratively is among the central factors determining the successful realization of educational goals and the positive development of children within an educational setting. Therefore, there is a pressing need to establish clear, measurable criteria for assessing the cooperation skills of preschool institution staff, particularly with consideration for innovative management approaches.